Accounting Perspective of Blessing in the Celebration of 1 Suro with Phenomenological Approach at Mount Kawi - Indana Novianti; Ana Sopanah; Syamsul Bahri (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2025)
Purpose: This research aims to explore the perspective of accounting for blessings in the 1 Suro cultural ritual in Mount Kawi, Malang, using a phenomenological approach. This research is motivated by a desire to understand accounting practices in the cultural and spiritual context that exists in society, particularly how blessings are interpreted not only materially but also through social and spiritual values. Methodology: The research methodology uses a qualitative phenomenological approach with data collection techniques through non-participant observation, in-depth interviews, and documentation of actors, ritual managers or customary leaders, and local communities involved in the 1 Suro celebration. Finding: The research findings indicate that there are local wisdom values contained in the 1 Suro ritual, namely Rembukan, Nguri-uru Kabudayan Leluhur, dan Tolak Balak. In addition, blessings are understood as harmony between humans, nature, and the creator, and reflected in the management of collective resources carried out with full values of cooperation, transparency, and spirituality. Accounting practices in this context are not only related to financial recording but also serve as a means of preserving values, social responsibility, and cultural accountability, hence it can be referred to as blessing accounting. Implication: The implications of this research expand the understanding of culturally-based accounting practices and encourage the integration of spiritual values into resource management systems. Originality: This research also provides originality in enriching the literature on cultural accounting in Indonesia and opens up space for the development of a holistic, sustainable model of accounting based on the local community's values.